2014
DOI: 10.7196/sajsm.526
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in 7 - 10-year-old children in urban primary schools in Port Elizabeth

Abstract: Objective. The primary aim of this study was to quantify the prevalence of overweight and obesity among urban 7 -10-year-old children in affluent (quintile 5) English-medium primary schools in Port Elizabeth. Method. A quantitative, descriptive one-way cross-sectional research design utilising random sampling was used. A once-off survey consisted of anthropometrical assessment of body mass index (BMI) according to standardised procedures. To classify children into weight categories, the International Obesity T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…For example in 10-to 14-year-old girls and boys, the combined prevalence of overweight and obesity were 23% and 10%, respectively, and in 15-to 17-year-old girls and boys, the prevalence were 27% and 9%, respectively. 9,47 Since the 2014 Report Card, in the absence of national data, regional studies corroborate the growing public health challenge of childhood overweight and obesity, 14,15,[48][49][50][51][53][54][55][56] especially among the girls and in urban areas. 14,49,57,58 Moreover, in a 20-year prospective study, South African boys who were obese at 4 to 8 years old were 19.7% times more likely to be obese at age 16 to 18 years, and girls who were obese at 4 to 8 years old were a staggering 42.3 times more likely to be obese at 16 to 18 years compared with nonobese children.…”
Section: Nutrition Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example in 10-to 14-year-old girls and boys, the combined prevalence of overweight and obesity were 23% and 10%, respectively, and in 15-to 17-year-old girls and boys, the prevalence were 27% and 9%, respectively. 9,47 Since the 2014 Report Card, in the absence of national data, regional studies corroborate the growing public health challenge of childhood overweight and obesity, 14,15,[48][49][50][51][53][54][55][56] especially among the girls and in urban areas. 14,49,57,58 Moreover, in a 20-year prospective study, South African boys who were obese at 4 to 8 years old were 19.7% times more likely to be obese at age 16 to 18 years, and girls who were obese at 4 to 8 years old were a staggering 42.3 times more likely to be obese at 16 to 18 years compared with nonobese children.…”
Section: Nutrition Indicatorsmentioning
confidence: 99%
“…The HealthKick study in 16 Schools in the Western Cape reported a small percentage of children eating take away foods the day before data collection, 62 while Feeley et al 51 reported that the nearly 1500 older adolescents interviewed in Soweto, consumed fast food items 11 times per week. The latter observation is corroborated by the Insight Survey's latest Fast Food Industry Landscape Report 2015 which states that "fast food is experiencing exponential growth with local consumers (16+ years old) increasing from 66% in 2009 to 80% in 2014.…”
Section: Nutrition Indicatorsmentioning
confidence: 99%
“…Height, weight and BMI of the children have been reported and discussed in detail elsewhere. [16] Table 3 illustrates descriptive data obtained for BMI and MET levels for the total group.…”
Section: Resultsmentioning
confidence: 99%
“…ANOVA indicated a significant difference in BMI IOTF z-scores between boys and girls (p<0.05) as reported in detail elsewhere. [16] The normative gender-specific IOTF cut-off criteria [11] were used to quantify obesity and overweight rates among participants. These values represent cut-off points chosen as percentiles that match adult cut-offs for BMI values.…”
Section: Resultsmentioning
confidence: 99%